(untitled) (Global Journal of Human-Social Science, 2023)
This study investigates how an urban 9th-grade Chinese bilingual algebra teacher s translanguaging and culturally relevant pedagogy fostered conceptual learning in mathematics for secondary bilingual students Results revealed that mathematical concepts could be discussed explored and reasoned by tapping into students multilingual multicultural and multimodal repertoires and their prior schooling and cognitive resources The bilingual mathematics teacher s in-depth understanding of the students home language and culture and previous literacy education experiences are key to motivating engaging and sustaining the students learning of mathematics Equally important is the teacher s willingness to use the students culturally familiar knowledge and the multimodal resource to create translanguaging opportunities to advance their learning of language and mathematics The interplay of languages literacy practices and mathematical thinking and reasoning is a powerful tool for bilingual students to learn both languages and subject matter knowledge